Pengaruh Budaya Organisasi, Gaji dan Tingkat Stres terhadap Employee Engagement di Puskesmas Sukawati 1 Gianyar - Siluh Nyoman Raita Sari; Erliany Syaodih; Yen Efawati (MAMEN: Jurnal Manajemen, 2025)
This study investigates the effects of organizational culture, salary, and stress levels on employee engagement at Puskesmas Sukawati 1 Gianyar. Employee engagement is widely recognized as a critical factor that influences productivity, commitment, and organizational performance, particularly in healthcare institutions where service quality depends heavily on staff involvement. The research employed a quantitative approach with a descriptive survey design, involving 80 employees as respondents. Data were collected through questionnaires and documentation, then analyzed using statistical methods to assess both partial and simultaneous relationships among the variables. The findings reveal that organizational culture, salary, and stress levels individually do not exert a significant influence on employee engagement. Similarly, the simultaneous analysis of the three variables shows no significant collective effect on engagement. These results suggest that other factors beyond organizational culture, salary, and stress may play a more substantial role in shaping employee engagement within the context of primary healthcare services. This study contributes to the understanding of employee engagement determinants in health organizations and provides insights for future research to explore additional variables that may strengthen workforce motivation, commitment, and performance in healthcare settings.